1998
DOI: 10.1902/jop.1998.69.10.1119
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Conditions and Salivary Immunoglobulins in Individuals With Down Syndrome

Abstract: Periodontal conditions and salivary levels of Immunoglobulins slgA, IgM, and IgG subclass distribution and albumin, quantified by enzyme‐linked immunosorbent assay, were determined in 20 patients with Down syndrome and 19 healthy controls. Gingival inflammation was more extensive (P < 0.05) among Down syndrome subjects compared to controls as well as the occurrence of periodontal pockets (< 4 mm) (P < 0.05). The immunoglobuhn levels of slgA, IgM, the sum of IgG subclasses, and the concentration of alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
4
17
0
2
Order By: Relevance
“…The median salivary IgA concentration in the study group was similar to that of the controls, while the median salivary IgG and IgM concentrations were higher by 25% and 340%, respectively. These findings are compatible with previously described Ig levels in whole saliva of DS subjects (Barr-Agholme et al, 1998). In the aforementioned study, however, no adjustment for flow rate was made.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The median salivary IgA concentration in the study group was similar to that of the controls, while the median salivary IgG and IgM concentrations were higher by 25% and 340%, respectively. These findings are compatible with previously described Ig levels in whole saliva of DS subjects (Barr-Agholme et al, 1998). In the aforementioned study, however, no adjustment for flow rate was made.…”
Section: Discussionsupporting
confidence: 93%
“…A review of the literature reveals sporadic studies concerned with the function of the DS MIS (Epstein and Baumgarten, 1991;Barr-Agholme et al, 1998). We therefore undertook to assess the levels of salivary immunoglobulins (Ig) in a group of DS individuals and its bearing on their susceptibility to mucosal surface infections.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was recently reported that 90.6% (29 of 32) of Down syndrome individuals aged 15-39 were calculus free, with a significant difference as compared to the greater amount of calculus accumulation in age/gender matched healthy controls [31]. Furthermore, other studies found no significant difference or less prevalence of calculus accumulation in Down syndrome subjects, as compared to healthy controls [32][33][34]. Despite poor oral hygiene, calculus deposits are likely to be reduced in Down syndrome individuals.…”
Section: Prevalence Of Periodontitis In Down Syndromementioning
confidence: 97%
“…In addition, IgG antibody titers to P. gingivalis , A actinomycetemcomitans, F. nucleatum, S. sputigena, and S. mitis correlated significantly with the modified PMA scores. Barr- Agholme et al (1998) investigated the clinical periodontal conditions and salivary immunoglobulins in patients with DS. The results showed an altered distribution of IgG subclasses in saliva, with an increased amount of IgG1 in DS patients compared to controls.…”
Section: Antibody/immunoglobulin Productionmentioning
confidence: 99%